Masters of the Structural Aesthetic - Thomas, Derek (Springer Singapore, 2018)
This book highlights aesthetics as pertaining to the structural component in architectural design. This less explored aspect of architecture is discussed and explains the enduring qualities of ten specific buildings from architectural history to present day due to their structural aesthetics. Based on comprehensive research, a critical analysis is presented of the constraints and other influences on architectural and structural design, such as culture, patronage, geometry, available resources and technologies.